Numerical investigation on the performance of coalescence and break-up kernels in subcooled boiling flows in vertical channels. (June 2017) - Vahaji, Sara; Cheung, Sherman CP; Deju, Lilunnahar; Yeoh, Guan; Tu, Jiyuan
In order to accurately predict the thermal hydraulic of two-phase gas–liquid flows with heat and mass transfer, special numerical considerations are required to capture the underlying physics: characteristics of the heat transfer and bubble dynamics taking place near the heated wall and the evolution of the bubble size distribution caused by the coalescence, break-up, and condensation processes in the bulk subcooled liquid. The evolution of the bubble size distribution is largely driven by the bubble coalescence and break-up mechanisms. In this paper, a numerical assessment on the performance of six different bubble coalescence and break-up kernels is carried out to investigate the bubble size distribution and its impact on local hydrodynamics. The resultant bubble size distributions are compared to achieve a better insight of the prediction mechanisms. Also, the void fraction, bubble Sauter mean diameter, and interfacial area concentration profiles are compared against the experimental data to ensure the validity of the models applied.